2015
DOI: 10.1039/c4ay02189d
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance FTIR database for the interpretation of the spectra obtained with a handheld device on built heritage materials

Abstract: FTIR handheld devices, working in the Diffuse Reflectance mode (DRIFT), are promising analytical instruments to perform in situ analyses on cultural heritage materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…In these cases, the use of Fourier Transform Infrared Spectroscopy (FTIR) is more indicated, since it avoids any problem related to the auto-fluorescence of the sample. Moreover, working with powdered samples, FTIR systems also ensure a better accuracy and repeatability of the results over the sample heterogeneities by sampling the whole corrosion system [23].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the use of Fourier Transform Infrared Spectroscopy (FTIR) is more indicated, since it avoids any problem related to the auto-fluorescence of the sample. Moreover, working with powdered samples, FTIR systems also ensure a better accuracy and repeatability of the results over the sample heterogeneities by sampling the whole corrosion system [23].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum relative to the white area (Figure 8c) clearly shows the features of calcite: 4270 cm -1 (3ν 3 (CO 3 ) 2-), 2515+2590 cm -1 doublet (ν 1 + ν 3 and/or 2ν 2 + ν 4 (CO 3 ) 2-), 1795 cm -1 (ν 1 + ν 4 (CO 3 ) 2-), 1400 cm -1 ca. strong absorption (ν 3 (CO 3 ) 2-) inverted by the reststrahlen effect, 880 cm -1 (ν 2 ) distorted in a derivative shape (48)(49)(50). The same features are more or less evident in the other DRIFT spectra, especially in that of the black spot (Figure 8a), and are highlighted with a dotted red line.…”
Section: Molecular Spectroscopy -Diffuse Reflectance Infrared Fouriermentioning
confidence: 68%
“…The combination bands (sum or difference of fundamental bands) are enhanced in reflection spectra. It has been shown that the ν1 + ν4 and ν1 + ν3 bands can be used to identify carbonates and for calcite the bands occur at 1800 cm − 1 and 2512 cm − 1 , respectively ( Arrizabalaga et al, 2015 ;Miliani et al, 2012). It is clear in Fig.…”
Section: Figmentioning
confidence: 81%
“…This is because FTIR reflectance results in a combination of reflection and transmission/absorbance FTIR spectra, which is not always as easy to interpret. However, the increasing availability of portable spectrometers, and the possibility to use reflectance FTIR spectroscopy as non-invasive tool in heritage studies, have resulted in a number of in situ FT-IR reflectance studies on heritage building material, pigments in wall paintings and synthetic alteration of artefacts (Arrizabalaga et al, 2015;Miliani et al, 2012 ;Conti et al, 2013). As far as we can ascertain, this is the first reported use of a portable reflectance FTIR instrument used for the analyses of rock art.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%